QUANTIFICAÇÃO DE MACRO E MICROELEMENTOS EM ARROZ NATIVO DO PANTANAL - Rafaela Henriques Rosa (2024)
Rice is a staple food for two-thirds of the world's population, with consumption growing especially in Asia, sub-Saharan Africa, Caribbean countries, and Latin America. The per capita consumption of rice in Brazil in 2021 was 39.8 kg, showing the relevance of this grain in Brazil. Although rice consumption provides important nutrients such as carbohydrates, other substances such as essential chemical elements and some toxic elements are also present. In this work, we determined the concentration of essential elements and potential toxic elements in different types of Brazilian rice grains, harvested or purchased using ICP-OES to identify their nutritional richness or their toxicity possibility. All rice were considered mineral sources of Mg, Mn, Mo, P, Se, and Zn, demonstrating that rice, as a staple food, can contribute to achieving adequate intake of essential nutrients. On the other hand, the main contaminant in the samples was arsenic, with a risk quotient greater than one for all rice samples. Furthermore, levels of copper above the established levels were found in several species, and native species were excessively contaminated with chromium, considering the risk quotients for these elements. Rice presents a dual classification: providing nutritional content and exposing possible risks of overexposure to toxic elements. Rice can be part of a healthy and nutritious diet, but more studies should be done on the possibility of avoiding or remedying contamination with toxic elements. Keywords: Pantaneiro rice, arroz-do-campo, chemical elements, toxicity.